2017
DOI: 10.1007/s11144-017-1161-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging time on the microstructural characteristics of a Cu/ZnO-based catalyst prepared by homogeneous precipitation for use in methanol steam reforming

Abstract: Nanocrystalline Cu-ZnO-based catalysts were successfully synthesized via a homogeneous precipitation method. Four aging times were used to prepare the catalysts (1, 3, 12 and 24 h) to study the influence on their textural, structural and catalytic properties. The samples were characterized by N 2 adsorption, powder X-ray diffraction, thermogravimetric analysis, H 2 temperature-programmed desorption and transmission electron microscopy, and the samples were applied to the steam reforming of methanol. The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Cu/ZnO is one of the most typical systems available in MSR, where ZnO serves to augment the dispersion and reduction of Cu catalysts and to stabilize the CuO. [16][17] The reduction of Cu in CuO/ZnO catalysts was investigated by H 2 -TPR by Fierro et al [18] It is revealed that the metallic copper formed by reduction of CuO was not reoxidized at the detectable level irrespective of the catalyst composition, indicating that the addition of ZnO enhances the reduction of CuO. Moreover, the synergistic interaction existing between ZnO and Cu facilitates the high activity of Cu catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu/ZnO is one of the most typical systems available in MSR, where ZnO serves to augment the dispersion and reduction of Cu catalysts and to stabilize the CuO. [16][17] The reduction of Cu in CuO/ZnO catalysts was investigated by H 2 -TPR by Fierro et al [18] It is revealed that the metallic copper formed by reduction of CuO was not reoxidized at the detectable level irrespective of the catalyst composition, indicating that the addition of ZnO enhances the reduction of CuO. Moreover, the synergistic interaction existing between ZnO and Cu facilitates the high activity of Cu catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is required to introduce co‐catalysts that enhance the dispersion and reduction of Cu catalysts. Cu/ZnO is one of the most typical systems available in MSR, where ZnO serves to augment the dispersion and reduction of Cu catalysts and to stabilize the CuO [16–17] . The reduction of Cu in CuO/ZnO catalysts was investigated by H 2 ‐TPR by Fierro et al [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, Cu-based catalysts (e.g. Cu/ZnO and Cu/ZnO/ Al 2 O 3 ) prepared by urea hydrolysis of nitrate salts have been reported for steam reforming of methanol, [20][21][22][23][24][25][26][27][28] water-gas shi reaction, [28][29][30][31][32] selective hydrogenation, [33][34][35][36] and liquid phase methanol synthesis from syngas. [37][38][39] Most studies have shown higher copper surface area, stronger metal-support interaction, and better catalytic performance for CO 2 -related reaction than conventional co-precipitated catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…During the aging process, uniform precipitates will transform into zincian malachite with high Zn incorporation, forming the porous structure of the catalysts. , Highly dispersed Cu–Zn mixed oxides are obtained after further calcination from precursors and ultimately reduced to active Cu/ZnO catalysts, while formation of the Cu–Zn interface at this stage is verified . High performance of the catalysts originating from the increasing Cu–Zn interfaces is reported in literatures. Numerous studies have investigated the effect of aging and calcination processes on final activities of the catalysts; however, studies on the precipitation process are rarely concerned. Given that the structural evolution of Cu/ZnO catalysts originates from initial precipitates , and special “chemical memory” phenomenon was early proved during the process for preparing Cu/ZnO catalysts, namely, the sensibility of reaction characteristics to reaction conditions including changes of temperatures, solution concentrations, and pH values, research works on the precipitation process are thus deemed very important.…”
Section: Introductionmentioning
confidence: 99%